2009
DOI: 10.1007/s00221-009-1862-x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and inhibitory action control: evidence from spontaneous eye blink rates

Abstract: The inhibitory control of actions has been claimed to rely on dopaminergic pathways. Given that this hypothesis is mainly based on patient and drug studies, some authors have questioned its validity and suggested that beneWcial eVects of dopaminergic stimulants on response inhibition may be limited to cases of suboptimal inhibitory functioning. We present evidence that, in carefully selected healthy adults, spontaneous eyeblink rate, a marker of central dopaminergic functioning, reliably predicts the eYciency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 69 publications
5
84
3
Order By: Relevance
“…It is regulated by the dopamine system and the increased rate of eye blinking along the pregnancy might be a parameter of the central dopamine system [39][40][41][42] (fig 2b). During pregnancy the rate increases until term when usually a slight decrease is observed [21,[34][35][36][37].…”
Section: Facial Expressionsmentioning
confidence: 99%
“…It is regulated by the dopamine system and the increased rate of eye blinking along the pregnancy might be a parameter of the central dopamine system [39][40][41][42] (fig 2b). During pregnancy the rate increases until term when usually a slight decrease is observed [21,[34][35][36][37].…”
Section: Facial Expressionsmentioning
confidence: 99%
“…One of the experimenters sat nearby to control the subjects who did not close their eyes; however, they had clearly understood the instruction and none of them closed the eyes. Blinks were recorded through 3 M Red Dot Ag/AgCl disposable electrodes placed on the right orbicularis muscle, amplified by a LACEElettronica System amplifier (Pisa, Italy) and stored for off-line analysis; the number of BR (voltage change of 100 uv in a time interval of 500 ms, according to Colzato et al 2009), was counted for each of the consecutive 5 min by a Labview software prepared ad hoc. Skin conductance (SC) was monitored by via 8 mm Ag/AgCl electrodes placed on the thenar and hypo-thenar regions of the right hand.…”
Section: Experimental Session and Data Acquisitionmentioning
confidence: 99%
“…In fact, cerebellar impairment is associated with higher BR and several studies of sensorimotor integration indicate different cerebellar controls in the highs' and lows' behavior. studies of functions classically considered as "dopaminergic" (Kohl et al 2013;Colzato et al 2009) have provided inconsistent results. In fact, reduced pre-pulse inhibition has been found associated with high hypnotisability (Lichtenberg et al 2008b), but blink rate (BR) has been found lower in highs than in medium hypnotizable individuals (mediums) (Lichtenberg et al 2008a) and lows (Lindsay et al 1993).…”
Section: Introductionmentioning
confidence: 96%
“…These patterns may be the expression of an intrinsic feature of each individual determined by mesencephalic dopaminergic activity. Although the hypothesis of blinking rate central regulation is well accepted in neuropsychology (4)(5)(6)(7)(8)(9) , there are several lines of ophthalmologic evidence showing that the condition of the ocular surface modulates the blink rate (1,(10)(11) . A classical example is the reduced blink rate that occurs after topical ocular anesthesia (12) .…”
mentioning
confidence: 99%